Quantitative characteristics of the neurotensin content in the hypothalamic arcuate nucleus in arterial hypertension of different etiologies - O. V. Hancheva; S. V. Tishсhenko; T. V. Ivanenko (Patologìâ)
The aim of this work is to determine the features of the neurotensin content in the hypothalamic ARC in Wistar rat and SHR strains in arterial hypertension of different etiology: endocrine-salt and essential.